SERUM ALBUMIN: AN INDEPENDENT INDICATOR IN GUILLAIN–BARRE SYNDROME PATIENTS RECEIVING TREATMENT OF PLASMAPHERESIS - FAYAZ , A; ABBASI , WZ; BUTT , US; AHMAD , A; ABDULLAH, .; AHMED , F (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to assess the role of serum albumin as an independent indicator in Guillain–Barre Syndrome patients receiving plasmapheresis treatment. This descriptive case series was conducted at Hayatabad Medical Complex Peshawar, Pakistan, from December 2022 to May 2023. Total 80 patients with GBS syndrome. Patients were divided into two groups equally. Group A patients had lower serum albumin, and group B had normal serum albumin. In both groups, serum albumin as an independent indicator was assessed. Chi-square and Independent T-tests were applied in both groups, keeping the P value less than 0.05. The mean age of the patients was 31.90±8.63 years. The frequency of male patients was 62.5%, while female patients were 37.5%. In group A, 27.5% of patients had good outcomes, while 75.5% had poor outcomes, while in group B, 57.5% had good outcomes, and 42.5% had outcomes. The outcome in group B was significantly better than in group A (P = 0.007). In the normal serum albumin group, the Guillain-Barre syndrome disability score was significantly lower after receiving plasmapheresis treatment than in patients with low serum albumin levels.